Liquid crystalline hydrazones revisited: dipolar interactions vs hydrogen bonding affecting mesomorphic properties. Issue 10 (9th August 2021) - Knelles, Jakob; Wanner, Chris; Schulz, Finn; Freund, Marcel; Kolmangadi, Mohamed A.; Baro, Angelika; Huber, Patrick; Schönhals, Andreas; Laschat, Sabine
ABSTRACT: In order to understand the role of dipolar interactions vs. H-bonding, a series of hydrazones were synthesised from 4-alkoxy-, 3, 4-dialkoxy- or 3, 4, 5-trialkoxybenzaldehydes and phenyl, bromo- or nitrophenylhydrazine, respectively. Their mesomorphic properties were investigated by differential scanning calorimetry (DSC), polarising optical microscopy (POM), X-ray diffraction (WAXS, SAXS) and compared with known members. Only those hydrazones derived from 3, 4, 5-trisalkoxybenzaldehyde and either meta, meta -dinitro- or ortho, para -dinitrophenylhydrazine displayed hexagonal columnar mesophases. All other derivatives were non-mesomorphic, even when H-bonds were present. Dipole moments of the various nitro-substituted hydrazones were experimentally determined by dielectric measurements and supported by theoretical DFT calculations, which indicated that the mesophase formation is mostly governed by strong dipole moment and further enforced by intramolecular H-bonding. Abstract : uf0001